2018
DOI: 10.1248/bpb.b17-00880
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Caco-2 Cell Line Carrying the Human Intestine-Type CES Expression Profile as a Promising Tool for Ester-Containing Drug Permeability Studies

Abstract: Carboxylesterase 2 (CES2), which is a member of the serine hydrolase superfamily, is primarily expressed in the human small intestine, where it plays an important role in the metabolism of ester-containing drugs. Therefore, to facilitate continued progress in ester-containing drug development, it is crucial to evaluate how CES2-mediated hydrolysis influences its intestinal permeability characteristics. Human colon carcinoma Caco-2 cells have long been widely used in drug permeability studies as an enterocyte m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…We next sought to compare our model to human colon carcinoma Caco-2 cells, widely considered the gold standard for assessing oral drug absorption and ADMETox studies 32 . Even though these cells are of colonic origin and share some features with small intestinal enterocytes, their transformed character and genomic instability raise doubts about their use for basic and translational research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next sought to compare our model to human colon carcinoma Caco-2 cells, widely considered the gold standard for assessing oral drug absorption and ADMETox studies 32 . Even though these cells are of colonic origin and share some features with small intestinal enterocytes, their transformed character and genomic instability raise doubts about their use for basic and translational research.…”
Section: Resultsmentioning
confidence: 99%
“…We next sought to compare our model to human colon carcinoma Caco-2 cells, widely considered the gold standard for assessing oral drug absorption and ADMETox studies 32 .…”
Section: Functionality Of Human Mini-colonsmentioning
confidence: 99%
“… 16 18 Expression of CES2 in the human intestine is well documented. 19 , 20 To delineate whether CES1 protein is expressed in human intestine, we performed western blot of human small bowel epithelial cell lysates prepared from intestinal resections of patients with inflammatory bowel disease. Both CES1 and CES2 were expressed in these lysates ( Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…The microarray analysis showed that the gene expression levels of carboxylesterase 1 ( CES1 ) were unexpectedly increased by PEPT1 knockout (Figure 3A). It is known that carboxylesterases catalyze the hydrolysis of esters, amides, thioesters, and carbamates 28, 29, 30. In humans, two carboxylesterases, CES1 and CES2, are important mediators of drug metabolism.…”
Section: Discussionmentioning
confidence: 99%